Foundations and Donations as a Link Between Croatia and the Dalmatian Cities in the Early Middle Ages - Budak, Neven (2005)
The author analysis a number of charters and other early medieval documents from Dalmatia, which reveal the links established between the Croatian elite and the Dalmatian towns through means of pious donations and foundations.
Projekt MZOS
ENG